From legends to legacy: the impact of fan influence on retiring athletes in premier league basketball - Lev, Assaf; Levental, Orr; Tamir, Ilan (Frontiers in Psychology, 2023)
The current research explores premier league basketball players' perceived age as they approach retirement, and the role of their fan base in this process. The study sheds light on the dialogue between older players and the audience. Based on semi-structured interviews with eleven professional Israeli basketball players and two veteran basketball players' agents, the research identifies three key themes that shape the relationship between the players and spectators with respect to players' ages: (a) a sense of betrayal and undue expectations; (b) acknowledgment of gratitude and acquiring a special status; and (c) the media's impact on the fan base's opinions. These themes reveal a common process wherein sports media portray veteran players as older adults, influencing fan perceptions positively and negatively, both on and off the court. The study's main argument is that "coercion" to retire from a professional sports career is more pronounced than in other life domains. This perception stems from the widely held belief, shared by the general public and athletes, that sports success is limited in duration and dependent on biological age, with a "young body" being a necessary condition for athletic achievements.